ATO (Arsenic Trioxide) Effects on Promyelocytic Leukemia Nuclear Bodies Reveals Antiviral Intervention Capacity. Issue 8 (27th February 2020) - Hofmann, Samuel; Mai, Julia; Masser, Sawinee; Groitl, Peter; Herrmann, Alexander; Sternsdorf, Thomas; Brack‐Werner, Ruth; Schreiner, Sabrina
Abstract: Human adenoviruses (HAdV) are associated with clinical symptoms such as gastroenteritis, keratoconjunctivitis, pneumonia, hepatitis, and encephalitis. In the absence of protective immunity, as in allogeneic bone marrow transplant patients, HAdV infections can become lethal. Alarmingly, various outbreaks of highly pathogenic, pneumotropic HAdV types have been recently reported, causing severe and lethal respiratory diseases. Effective drugs for treatment of HAdV infections are still lacking. The repurposing of drugs approved for other indications is a valuable alternative for the development of new antiviral therapies and is less risky and costly than de novo development. Arsenic trioxide (ATO) is approved for treatment of acute promyelocytic leukemia. Here, it is shown that ATO is a potent inhibitor of HAdV. ATO treatment blocks virus expression and replication by reducing the number and integrity of promyelocytic leukemia (PML) nuclear bodies, important subnuclear structures for HAdV replication. Modification of HAdV proteins with small ubiquitin‐like modifiers (SUMO) is also key to HAdV replication. ATO reduces levels of viral SUMO‐E2A protein, while increasing SUMO‐PML, suggesting that ATO interferes with SUMOylation of proteins crucial for HAdV replication. It is concluded that ATO targets cellular processes key to HAdV replication and is relevant for the development of antiviral intervention strategies. Abstract : Arsenic trioxide (ATO) treatment significantly represses efficient human adenovirus (HAdV) infection at low micromolar concentrations, involving reconstitution of dot‐like promyelocytic leukemia nuclear body structures, which thereby maintain their antiviral function. Intervention of dsDNA virus gene expression and replication by improving the host antiviral defense mechanisms provide a novel basis for innovative antiviral strategies in future therapeutic settings.